A recommendation for naming proteins in Neurospora - Jay C. Dunlap; Matthew Sachs; Jennifer Loros (Fungal Genetics Reports, 1996)
The issue of gene product names is important in as much as it promotes consistency within the literature and promotes accessibility of the Neurospora literature to readers more familiar with other organisms.